A SYSTEMATIC LITERATURE REVIEW OF 21ST-CENTURY DIGITAL LEARNING TRENDS AND TEACHERS’ TECHNOLOGY INTEGRATION - Radhiani, Ahyani; Sriayu, Sriayu; Arqam, Muh; Abouseada, Farouk; RS, Asmaul Husna (LPPM Universitas Jambi, 2026)
The rapid advancement of digital technology has reshaped communication, information access, and knowledge construction. In education, its integration into 21st-century learning is central to enhancing quality and relevance. Educational institutions worldwide are increasingly adopting digital tools to enrich learning experiences, with digital learning defined as the use of technology and devices to support more engaging, explorative, and interactive learning. This study aimed to determine contemporary trends and developments in 21st-century digital learning through a systematic literature review conducted in accordance with the PRISMA guidelines. A total of 56 articles, published between 2020 and mid-2025 and retrieved from the Scopus database based on predetermined inclusion criteria, were analysed. The findings underscore the critical role of digital technologies in enhancing learning practices. Results indicate that scholarly attention to digital learning peaked in 2024, as evidenced by a notable increase in publications. The majority of research contributions originated from Asia, with digital learning most extensively implemented in higher education institutions. From a scientific perspective, STEM fields were identified as the most frequent adopters of digital technologies in their learning practices. Among the various technological tools employed, game-based learning emerged as the most prevalent, demonstrating substantial contributions to learning effectiveness. Furthermore, the integration of digital technologies into educational contexts was found to enhance learning outcomes, problem-solving abilities, motivation, and students’ character and literacy development. Collectively, these findings provide a comprehensive overview of current trends in the application of digital technologies in education and offer valuable insights for policymakers in formulating effective technology-based educational strategies.